Populisme Dan Dinamika Otoritas Keagamaan Dalam Islam Di Media Sosial - Nur Afni Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The research is used to answer three main problems, namely what are the discourses behind Felix Siauww's appearance on social media such as YouTube and Instagram, how is the narrative of Islamic Populism discourse built by Felix Siauww on Instagram, and how YouTube media builds and strengthens Felix Siauww's religious authority. The researcher used the visual ethnographic method offered by Cristine. Data collection is done by combining empirical and theoretical data that is devoted to social media which is devoted to Felix Siauww's Instagram account and YouTube Channel. The results of Felix Siauww's research maximize the sophistication of social media, namely by paying attention to aspects of ethical values, character, and aesthetics. There are three reasons to mention Felix Siauww as a representation of Islamic populism among Netizens; First, Islamic populism is synonymous with anti-establishment terminology. second, Islamic populism is synonymous with anti-authoritarian narratives, third, populism contains narratives of religious purification and calls for a return to true teachings.